2018
DOI: 10.1111/jgh.14518
|View full text |Cite
|
Sign up to set email alerts
|

Circulating inflammation‐related markers and advanced gastric premalignant lesions

Abstract: Background and Aim Chronic Helicobacter pylori infection causes gastric mucosal inflammation as an important antecedent of gastric cancer. We aimed to evaluate associations of blood markers of inflammation with gastric intestinal metaplasia and dysplasia in H. pylori‐infected individuals. Methods We compared pre‐treatment serum levels of immune‐related and inflammation‐related markers between 99 individuals with intestinal metaplasia or dysplasia and 75 control individuals with non‐atrophic gastritis within an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…This assumption is supported by a study in which increased systemic levels of IL-10 and decreased levels of IL-4 have been found investigating EAC and ESCC together [21]. Conversely, in gastric cancers increased levels of both serum IL-10 and IL-4 have been reported [22][23][24][25][26]. These findings emphasize the use of both systemic IL-10 and IL-4 as potential biomarkers in EACs.…”
Section: Plos Onementioning
confidence: 63%
See 1 more Smart Citation
“…This assumption is supported by a study in which increased systemic levels of IL-10 and decreased levels of IL-4 have been found investigating EAC and ESCC together [21]. Conversely, in gastric cancers increased levels of both serum IL-10 and IL-4 have been reported [22][23][24][25][26]. These findings emphasize the use of both systemic IL-10 and IL-4 as potential biomarkers in EACs.…”
Section: Plos Onementioning
confidence: 63%
“…On the other hand, anti-inflammatory cytokines like IL-4 and IL-10 have a predominantly regulatory function in the immune system [19,20]. Increased as well as decreased levels of IL-4 and IL-10 have been reported in esophageal and gastric cancers and their prognostic value remains uncertain [21][22][23][24][25][26]. However, one meta-analysis identified serum IL-10 as a negative prognostic marker in several gastrointestinal malignancies including colon and gastric cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it has been put forward that systemic elevation of Th2 cytokines, observed here particularly in gastric cancer, may indicate a generalized state of immunosuppression and still promote cancer growth and dissemination [ 36 ]. Different association patterns for local and systemic IL-4, concerning sex-dependence [ 15 , 37 ] and relation with the disease advancement [ 13 , 14 ], have been noted also by other authors. Regarding CRC, previous studies have shown circulating IL-4 to be too low to be quantified [ 38 ] or, in contrary, elevated [ 39 , 40 , 41 ] and suitable as a CRC biomarker.…”
Section: Discussionmentioning
confidence: 84%
“…However, available literature data concerning IL-4 and IL-13 in CRC and upper GIT cancers are fragmentary and frequently inconsistent. Contradicting findings have been reported, especially concerning the interleukins’ status at local and systemic level and their association with the disease advancement [ 13 , 14 , 15 ]. Consequently, both tumor promoting [ 10 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] and protective roles [ 14 , 15 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ] have been advocated for IL-4 and IL-13.…”
Section: Introductionmentioning
confidence: 99%
“…It is commonly known that chronic inflammatory status, caused by Helicobacter pylori infection [ 7 ] or laryngopharyngeal reflux [ 8 ] and other incentives, is a long-term factor in laryngeal lesions. Previous researches described the potential interrelation between systematic markers and local inflammation [ 9 ], and peripheral blood markers had been applied to evaluate the clinical responses of many diseases, including advanced colorectal neoplasia [ 10 ], gastric premalignant lesions [ 11 ], gynecological cancers [ 12 ], and the precancerous laryngeal lesions [ 13 , 14 ]. Our previous research focused on the horizontal comparison of VFL with benign and malignant lesions of vocal cord and managed to find significant markers [ 15 ]; however, few investigations were made in the longitudinal and self-control comparison methods.…”
Section: Introductionmentioning
confidence: 99%